Recomendaciones para el uso del nuevo herbicida pre-emergente "GOAL" en yuca - Leihner, D.E.; Domínguez, J.; Kano, Y; López, J. (International Center for Tropical Agriculture, 1979)
Observations and recommendations on the use of the herbicide oxyfluorfen are included on the basis of research conducted at the Centro Internacional de Agricultura Tropical (CIAT) on its efficiency in selective weed control in cassava, effect on yield, rates of application, and possible combinations with other products. (CIAT)